2022
DOI: 10.1186/s12877-021-02737-2
|View full text |Cite
|
Sign up to set email alerts
|

Positive health during the COVID-19 pandemic: a survey among community-dwelling older individuals in the Netherlands

Abstract: Background Coronavirus Disease 2019 (COVID-19) reached the Netherlands in February 2020. To minimize the spread of the virus, the Dutch government announced an “intelligent lockdown”. Older individuals were urged to socially isolate completely, because they are at risk of a severe disease course. Although isolation reduces the medical impact of the virus, the non-medical impact should also be considered. Aim To investigate the impact of COVID-19 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…In line with what we found, a recent study in the Netherlands among older adults indicated that the majority of participants reported that their meaning in life remained unchanged during the beginning of the COVID-19 pandemic [21]. Tis suggests that many older adults were resilient and adaptive during the COVID-19 pandemic, which might have helped them to cope with the crisis situation.…”
Section: Discussionsupporting
confidence: 90%
“…In line with what we found, a recent study in the Netherlands among older adults indicated that the majority of participants reported that their meaning in life remained unchanged during the beginning of the COVID-19 pandemic [21]. Tis suggests that many older adults were resilient and adaptive during the COVID-19 pandemic, which might have helped them to cope with the crisis situation.…”
Section: Discussionsupporting
confidence: 90%
“…Compared with our earlier cross-sectional study at the end of the first wave, 11 this study showed a similarrated impact on Positive Health, with the exception of common initial improvements in areas such as mental well-being reported in our earlier study. This seems to suggest that rather than more prevalent adverse impacts across more dimensions, the second wave of the pandemic and associated increasingly strict preventive measures 4 was mainly characterized by the absence of previously experienced improvements in certain dimensions.…”
Section: Discussionsupporting
confidence: 79%
“…Trends across groups were tested by Jonckheere-Terpstra and linear by linear Chisquare tests, as appropriate. Logistic regression models were applied, both crude and adjusted for age and sex, 11,20 to assess dependency on these covariates in the risk of self-rated decrease in Positive Health for those with mild and complex health problems versus those without health problems. To explore additional differences based on use of preventive measures, those with high and low use were compared by Pearson Chi-square tests, overall and in the above subgroups based on complexity of health problems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations